Factors influencing Malawian women's willingness to self-collect samples for human papillomavirus testing. Issue 2 (4th March 2016) - Esber, Allahna; McRee, Annie-Laurie; Norris Turner, Abigail; Phuka, John; Norris, Alison
Abstract : Background: Malawi has the highest incidence of cervical cancer in the world. Only 3% of Malawian women have ever been screened for cervical cancer. Self-collection of samples for human papillomavirus (HPV) testing could increase screening among under-screened and hard-to-reach populations. However, little is known about the acceptability of self-collection in rural African settings. Aim: We aimed to characterise Malawian women's willingness to self-collect vaginal samples for HPV testing and to identify potential barriers. Design: We used data from the baseline wave of a community-based cohort study, collected from July 2014 to February 2015. Setting: Participants were enrolled from the catchment area of a clinic in rural Lilongwe District, Malawi. Methods: We enrolled women aged 15–39 years ( n =824). Participants answered questions assessing willingness to self-collect a sample for HPV testing, concerns about testing and other hypothesised correlates of willingness to self-collect. Results: Two-thirds (67%) of the women reported willingness to self-collect a vaginal sample in their homes. Awareness of cervical cancer, supportive subjective norms, perceived behavioural control, and clinician recommendations were all positively associated with increased willingness to self-collect samples for HPV testing. Identified barriers to self-testing endorsed by women included: concerns that the test might hurt (22%), that they might not do the test correctly (21%), and that the test might not be accurate (17%). Conclusions: This study suggests that self-collection for HPV testing could be an acceptable cervical cancer screening method in this rural population. Findings identify modifiable beliefs and barriers that can inform the development of effective screening programmes.